2001
DOI: 10.1046/j.1365-2869.2001.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow‐release caffeine as a countermeasure to driver sleepiness induced by partial sleep deprivation

Abstract: The effect of partial sleep deprivation (PSD) on driving abilities, as measured with a driving simulator, and the value of slow‐release caffeine as a countermeasure to the expected performance decrements, were studied. Twelve subjects, between 20 and 25 years of age, underwent four experimental conditions, 4.5 or 7.5 h time in bed (TIB) with 300 mg slow‐release caffeine or placebo, according to a Latin square design. Driving performance was measured twice by a 45‐min driving task on a simulator. Subjective sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 31 publications
(45 reference statements)
0
60
0
Order By: Relevance
“…That increased physiological sleepiness can cause impaired psychomotor performance has been shown in human extended-wakefulness studies (De Gennaro et al, 2001;Nakano et al, 2000;Thomas et al, 2000), shift-work model (Porcu et al, 1998), a clinicopathologic survey for disorders characterized by excessive daytime sleepiness (Cohen-Zion et al, 2001;Hood and Bruck, 1996;Kinnari et al, 2000;Schulz et al, 1997), and a clinicopharmacological survey of alertness-modifying drugs such as caffeine, modafinil, and melatonin (De Valck and Cluydts, 2001;Nave et al, 2002;Wesensten et al, 2002). Although it remains unclear whether impaired psychomotor performance after DZP administration could also be caused by increased sleepiness, the magnitude of heat loss induced by Bz agonist may be a potent indicator to predict sedative effects on brain function.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…That increased physiological sleepiness can cause impaired psychomotor performance has been shown in human extended-wakefulness studies (De Gennaro et al, 2001;Nakano et al, 2000;Thomas et al, 2000), shift-work model (Porcu et al, 1998), a clinicopathologic survey for disorders characterized by excessive daytime sleepiness (Cohen-Zion et al, 2001;Hood and Bruck, 1996;Kinnari et al, 2000;Schulz et al, 1997), and a clinicopharmacological survey of alertness-modifying drugs such as caffeine, modafinil, and melatonin (De Valck and Cluydts, 2001;Nave et al, 2002;Wesensten et al, 2002). Although it remains unclear whether impaired psychomotor performance after DZP administration could also be caused by increased sleepiness, the magnitude of heat loss induced by Bz agonist may be a potent indicator to predict sedative effects on brain function.…”
Section: Commentmentioning
confidence: 99%
“…Recent studies have shown that the sleep-producing mechanism in humans is preceded by increased heat loss (Campbell and Broughton, 1994;Gilbert et al, 1999;Krauchi et al, 1999Krauchi et al, , 1997 and that various sleep-producing manipulations act, at least in part, by enhancing the heat loss mechanism (Deacon et al, 1994;Dorsey et al, 1999;Gilbert et al, 1999;Krauchi et al, 1999). Furthermore, physiological sleepiness has been shown to cause a decrease in psychomotor performance (De Gennaro et al, 2001;De Valck and Cluydts, 2001;Hood and Bruck, 1996;Kinnari et al, 2000;Nakano et al, 2000;Nave et al, 2002;Porcu et al, 1998;Schulz et al, 1997;Thomas et al, 2000;Wesensten et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Convergent studies have shown the positive effects of caffeine on alertness and performance during daytime as well as during night time [46][47][48][49] . These effects can be felt as soon as a moderate amount of caffeine (between 2 and 4 mg/kg) is taken, whatever its shape (coffee, tea or energy drink) 50) .…”
Section: Intake Of Natural or Pharmacological Substancesmentioning
confidence: 99%
“…The efficacy of the delivery of slow-release caffeine alone is fairly well documented [3,[21][22][23]. However, an assessment of safety and tolerability of prolonged use of slow-release energy supplements is lacking.…”
Section: Introductionmentioning
confidence: 99%